Efektivitas Game-Based Learning Berbasis Permainan Dadu dalam Meningkatkan Pemahaman Materi Peluang - Erawati, Ni Ketut; Purdaningsih, Luh Gede (Adi Widya: Jurnal Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of Game-Based Learning using dice games in improving sixth-grade elementary students’ understanding of probability concepts. The study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 28 students. Data were collected through concept understanding tests and observation sheets of student activities. The data were analyzed using both quantitative and qualitative approaches to provide a comprehensive description of students’ learning outcomes and engagement. The results indicate a significant improvement in students’ conceptual understanding of probability. The mean score increased from 73.32 in the pre-cycle to 78.79 in Cycle I and further improved to 85.29 in Cycle II. In addition, classical learning mastery reached 100% in Cycle II. Student activity also improved from moderately active to active and highly active, reflecting enhanced behavioral, emotional, and cognitive engagement during the learning process. These findings suggest that the implementation of Game-Based Learning using dice games creates an interactive, contextual, and meaningful learning environment. This approach effectively supports students in understanding abstract probability concepts through direct experience and enhances their overall engagement in mathematics learning. Keywords: game-based learning, probability, conceptual understanding, student activity, mathematics learning.